Mensuração da criação de valor social em uma escola de aprendizagem cooperativa - Lopes, Rennan Luz (2024)
This work aims to measure the social value of a public school that systematically uses the cooperative learning methodology. Although there are hundreds of studies published in the last 5 years on social value and cooperative learning, which demonstrates the relevance of the subjects, none of them directly relates these two themes. It is believed that this type of learning methodology promotes the development of more capabilities and freedoms. Then, this work proposes a measurement of social value as prescribed by Anand et al. (2009). This research used a quantitative approach, applying surveys based on questionnaires under development for measuring social value creation and the use of cooperative learning. The survey was applied in all three grades of EEEP Alan Pinho Tabosa and, as a control group, with people who participated of the Prece Moviment. This research contributes to expanding literature on the subject, acts as a source of demonstration of the results delivered by the organization under study, serves as a model or inspiration for institutions to assess their social value and/or increase their pedagogical proposal with the use of cooperative learning and, finally, contributes to the formulation of public policies for more inclusive, full-time schools and with integral education. Among the results, it was found that there is a positive correlation between indices of social value and cooperative learning; among the courses offered at Alan Pinho, the academic course showed a higher social value index; concerning social value constructs, the Alan Pinho presented the following highlights: discrimination outside work/school, religious freedom, freedom of thought and freedom of political expression. Finally, this research points out that the use of cooperative learning not only improves students' academic performance, but also contributes to a more inclusive, integral, democratic education with a greater perception of social value.